2016
DOI: 10.1111/ane.12574
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world data on eslicarbazepine acetate as add‐on to antiepileptic monotherapy

Abstract: ObjectiveTo assess retention, tolerability, and safety, efficacy and effects on quality of life (QoL) of eslicarbazepine acetate (ESL) add‐on treatment over 6 months in a real‐world adult population with partial‐onset seizures.MethodsThis non‐interventional, multicenter, prospective study was performed in eight European countries. Adult patients (n = 247) for whom the physician had decided to initiate ESL as add‐on to an existing antiepileptic drug (AED) monotherapy were invited to participate. The study compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
3
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 16 publications
5
25
3
2
Order By: Relevance
“…These results are in accordance with EPOS study,17 in which VPA and CBZ were also the concomitant AEDs presenting the greatest percentage of responders.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results are in accordance with EPOS study,17 in which VPA and CBZ were also the concomitant AEDs presenting the greatest percentage of responders.…”
Section: Discussionsupporting
confidence: 92%
“…The overall rate of AEs in our study was 23.1%. Compared to other studies that use ESL as adjunctive therapy, this rate is lower than the ones reported in EPOS study (26.0%),17 Correia et al. (42.1%),16 and that obtained in a pooled analysis of three phase III trials (62.7% and 67.5% in the ESL 800 mg and 1.200 mg groups, respectively) 9.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations